Horismenus species (Hymenoptera: Eulophidae) in a bruchid beetle parasitoid guild, including the description of a new species - Hansson, Christer; Aebi, Alexandre; Benrey, Betty (Zootaxa, 2004)
Four species of Horismenus (Hymenoptera: Eulophidae) associated with Acanthoscelides spp. (Coleoptera: Bruchidae), three of which are also associated with Phaseolus spp., are treated. One of the species, H. butcheri, is described as new and the remaining three species are redescribed. All four species are diagnosed in a key. A lectotype is designated for Holcopelte productus Ashmead.